Answer:
![\boxed{-3(x+3)(x^2-6x+10)}](https://tex.z-dn.net/?f=%5Cboxed%7B-3%28x%2B3%29%28x%5E2-6x%2B10%29%7D)
Step-by-step explanation:
Hello,
As the polynomial has only real coefficients, it means that 3-i is a zero too, because we apply the Conjugate Zeros Theorem.
It means that we can write the expression as below, k being a real number that we will have to identify.
![k(x+3)(x-3-i)(x-3+i)=k(x+3)((x-3)^2-i^2)\\\\=k(x+3)(x^2-6x+9+1)\\\\=k(x+3)(x^2-6x+10)](https://tex.z-dn.net/?f=k%28x%2B3%29%28x-3-i%29%28x-3%2Bi%29%3Dk%28x%2B3%29%28%28x-3%29%5E2-i%5E2%29%5C%5C%5C%5C%3Dk%28x%2B3%29%28x%5E2-6x%2B9%2B1%29%5C%5C%5C%5C%3Dk%28x%2B3%29%28x%5E2-6x%2B10%29)
And for x = 0, y = -90 so we can write
-90=k*3*10, meaning that k=-3
Hope this helps.
Do not hesitate if you need further explanation.
Thank you
Answer:
11.)
We can let the scores we don't know by x, and we know that tokay had 14 more points than Lodi. This can be shown as the following:
x + (x+14) = 162
2x+14=162
162-14= 148
148/2 = 74
Therefore Lodi scored 74 points.
12.)
We can substitute the prices we don't know by x and have the following:
4x+x=6.50
5x=6.50
6.50/5= 1.3
4x1.3= 5.2
Therefore the sandwich cost $5.20 and the drink costs $1.30
Answer:
17.01
Step-by-step explanation:
you do subvert them so you get 17.01
(f+g)(x) is 3x^2 + 3x/2 - 9
(f+g)(x)=f(x)+g(x)=x/2-3+3x^2+x-6= 3x^2 + 3x/2- 9